2015
DOI: 10.2139/ssrn.2660714
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Evidence-Based Persuasion Principles: An Application of the Index Method

Abstract: Purpose: To test whether a structured application of persuasion principles might help improve advertising decisions. Evidence-based principles are currently used to improve decisions in other complex situations, such as those faced in engineering and medicine.Approach: Scores were calculated from the ratings of 17 self-trained novices who rated 96 matched pairs of print advertisements for adherence to evidence-based persuasion principles. Predictions from traditional methods-10,809 unaided judgments from novic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…He divided his 195 principles into strategies, general tactics, and tactics specific to certain media. In subsequent studies, Armstrong et al (2016) found evidences of validity for the instrument, in addition to testing its predictive validity and demonstrating the potential of its use for advertising testing. Although the instrument has shown promise, more rigorous tests, using data from a single source, still need to be conducted (SHARP; HARTNETT, 2016).…”
Section: Possibilities Of Use In the Advertising Environmentmentioning
confidence: 93%
“…He divided his 195 principles into strategies, general tactics, and tactics specific to certain media. In subsequent studies, Armstrong et al (2016) found evidences of validity for the instrument, in addition to testing its predictive validity and demonstrating the potential of its use for advertising testing. Although the instrument has shown promise, more rigorous tests, using data from a single source, still need to be conducted (SHARP; HARTNETT, 2016).…”
Section: Possibilities Of Use In the Advertising Environmentmentioning
confidence: 93%
“…
Purpose -This study aims to independently test the predictive validity of the Persuasion Principles Index (PPI) for video advertisements for low-involvement products with a measure of in-market sales effectiveness. This study follows the inaugural test conducted by Armstrong et al (2016) for print advertisements for highinvolvement utilitarian products with a measure of advertising recall.Design/methodology/approach -The method was in line with that developed by Armstrong et al(2016) for rating advertisements and assessing the reliability of ratings. Consensus PPI scores were calculated for a data set of 242 matched pairs of television advertisements.
…”
mentioning
confidence: 99%
“…Findings indicate that better adherence to the persuasion principles produces only a weak, positive effect for predicting the performance of television advertisements for low-involvement products. A research agenda that flows from the results is discussed.Practical implications -The authors suggest that the PPI in its present form is best used to predict advertising performance under conditions as per the inaugural validation test (Armstrong et al, 2016).Originality/value -Advertisers will require compelling evidence of the PPI's predictive accuracy to adopt the tool for pre-testing advertising. This study is the first independent test of the predictive validity of the PPI and its generalisability across advertising conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations